Risk factors for avian influenza virus in backyard poultry flocks and environments in Zhejiang Province, China: a cross-sectional study - Xiao-Xiao Wang; Wei Cheng; Zhao Yu; She-Lan Liu; Hai-Yan Mao; En-Fu Chen (BMC, 2018)
Abstract Background Human infection of avian influenza virus (AIV) remains a great concern. Although live poultry markets are believed to be associated with human infections, ever more infections have been reported in rural areas with backyard poultry, especially in the fifth epidemic of H7N9. However, limited information is available on backyard poultry infection and surrounding environmental contamination. Methods Two surveillance systems and a field survey were used to collect data and samples in Zhejiang Province. In total, 4538 samples were collected by surveillance systems and 3171 from the field survey between May 2015 and May 2017, while 352 backyard poultry owners were interviewed in May 2017 by questionnaire to investigate factors influencing the prevalence of avian influenza A virus and other AIV subtypes. RT-PCR was used to test the nucleic acids of viruses. ArcGIS 10.1 software was used to generate maps. Univariate and logistic regression analyses were conducted to identify risk factors for AIV infection. Results Of the 428 poultry premises observed by the surveillance system, 53 (12.38%) were positive for influenza A virus. Of the 352 samples from poultry premises observed by field survey, 13 (3.39%) were positive for influenza A virus. The prevalence of AIV was unevenly distributed and the dominant subtype differed among cities. Eastern (Shaoxing and Ningbo) and southern (Wenzhou) cities exhibited a higher prevalence of AIV (16.33, 8.94, and 7.30% respectively). Contamination of AIV subtypes was most severe in January, especially in 2016 (23.26%, 70/301). The positive rate of subtype H5/H7/H9 was 2.53% (115/4538). Subtype H5 was the least prevalent, while subtypes H7 and H9 had similar positivity rates (1.50 and 1.32% respectively). Poultry flocks and environmental samples had a similar prevalence of AIV (4.46% vs 5.06%). The type of live birds was a risk factor and the sanitary condition of the setting was a protective factor against influenza A contamination. Conclusions AIV subtypes were prevalent in backyard poultry flocks and surrounding environments in Zhejiang Province. The types of live birds and sanitary conditions of the environment were associated with influenza A contamination. These findings shine a light on the characteristics of contamination of AIV subtypes and emphasize the importance of reducing AIV circulation in backyard poultry settings.